Strategi Komunikasi Pemasaran Unit Susu Koperasi Pemasaran Mitra Jaya Mandiri Kepada Konsumen Akhir Dalam Meningkatkan Penjualan Susu Sapi Perah - Ami Purnamawati; Rasty Astuti (LPPM Universitas Koperasi Indonesia, 2026)
Koperasi Pemasaran Mitra Jaya Mandiri Ciwidey as a marketing cooperative focused on managing and selling fresh cow’s milk produced by its member farmers. The milk business unit faces some challenges in increasing sales volume. One of the problems addressed in this study is the suboptimal marketing communication strategy, which has not yet reached end consumers broadly and sustainably. Although the cooperative has established close relationships with consumers, the communication approach used is still unstructured and has not fully leveraged the potential of other promotional media. This study aims to analyze the marketing communication strategies applied by the cooperative to increase the sales of fresh cow’s milk to end consumers. The communication strategies examined include Public Relations, Personal Selling, and Direct Marketing. Data were collected through questionnaires from end-consumer respondents and analyzed using descriptive statistical tabulation. The results indicate that Personal Selling is the most effective communication dimension in influencing purchasing decisions, while Public Relations requires improvement, particularly in delivering product information. Direct Marketing is proven effective in facilitating access to product information and ordering for consumers. Overall, the communication strategies implemented by the cooperative increase sales volume, but the purchase frequency still needs to be enhanced through additional strategies, such as regular promotions or loyalty programs